2008
DOI: 10.1093/hmg/ddn139
|View full text |Cite
|
Sign up to set email alerts
|

Activated caspase-6 and caspase-6-cleaved fragments of huntingtin specifically colocalize in the nucleus

Abstract: Proteolysis of mutant huntingtin is crucial to the development of Huntington disease (HD). Specifically preventing proteolysis at the capase-6 (C6) consensus sequence at amino acid 586 of mutant huntingtin prevents the development of behavioural, motor and neuropathological features in a mouse model of HD. However, the mechanism underlying the selective toxicity of the 586 amino acid cleavage event is currently unknown. We have examined the subcellular localization of different caspase proteolytic fragments of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 65 publications
2
100
1
Order By: Relevance
“…34 This finding is also in agreement with genetic studies in drosophilla that established that DJ-1 is critical for mitochondrial function. 31 Cysteine 106 is functionally essential for DJ-1 function and is also subject to oxidation. An interesting observation of the present study is that stable expression of DJ-1 Nt in SH-SY5Y cell line alters the oxidation level of both native and cleaved DJ-1.…”
Section: Discussionmentioning
confidence: 99%
“…34 This finding is also in agreement with genetic studies in drosophilla that established that DJ-1 is critical for mitochondrial function. 31 Cysteine 106 is functionally essential for DJ-1 function and is also subject to oxidation. An interesting observation of the present study is that stable expression of DJ-1 Nt in SH-SY5Y cell line alters the oxidation level of both native and cleaved DJ-1.…”
Section: Discussionmentioning
confidence: 99%
“…The drawbacks of these models are the loss of the natural genomic and protein context of the polyglutamine expansion, which could lead to altered regulation and a loss of potential disease-modifying post-translational modifications and protein interactions. Additionally, it has been shown that mHTT fragments generated by intracellular cleavage have a different subcellular localisation than truncated mHTT (Warby et al, 2008). It is therefore possible that the process of mHTT cleavage is in itself relevant to the pathogenesis of HD.…”
Section: Huntingtin Fragment Mouse Modelsmentioning
confidence: 99%
“…47 This allows easy detection of the mutant HTT 586 fragment without any other cleavage events occurring. We co-transfected 1212 128Q 4C HTT with WT CASP6 or mutant CASP6 C264/277S and found a significant~12% increase in cleavage of mutant HTT and generation of the 586 HTT fragment by palmitoylationdeficient CASP6 compared with WT ( Figure 3e).…”
Section: Resultsmentioning
confidence: 99%
“…The N-terminal 1212 amino acids of HTT with 128Q and the 4C mutations (D513A, D530A D552A, and D589A) were transiently transfected and overexpressed together with WT CASP6 or mutant CASP6 C264/277S in COS7 cells for 24 h. 47 Cell pellets from COS7 cells or Q111 and Q7 cells were lysed with SDP+ lysis buffer 65 and diluted in SDP+ lysis buffer to a final protein concentration of 2 μg/μl. 66,67 The detection of the 586 HTT fragment was performed using a combination of the monoclonal BKP1 antibody raised against the HTT N-terminus and an in-house 586 neo-epitope antibody raised against the C-terminus of 586 cleaved HTT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation